2020
DOI: 10.1103/physrevb.102.014516
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and superconductivity of calcium borohyrides at extreme pressures

Abstract: Motivated by the recent discovery of near-room temperature superconductivity in high-pressure superhydrides, we investigate from first principles the high-pressure superconducting phase diagram of the ternary Ca-B-H system, using ab initio evolutionary crystal structure prediction, and Density Functional Perturbation Theory. We find that below 100 GPa all stable and weakly metastable phases are insulating. This pressure marks the appearance of several new chemically-forbidden phases on the hull of stability, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 74 publications
2
54
0
Order By: Relevance
“…Basically, the Eliashberg spectral function depends on the dense k-points; namely, the dense k-points mesh contained all k and k+q grid points, which were covered by the q-points mesh. These conditions of the q-points and the calculated spectral function have been successfully reported in the previous DFT studies 29 , 30 . Therefore, a 8 4 16 k -points and 2 2 2 q -points computed in the first Brillouin zone (BZ) were used.…”
Section: Methodssupporting
confidence: 63%
“…Basically, the Eliashberg spectral function depends on the dense k-points; namely, the dense k-points mesh contained all k and k+q grid points, which were covered by the q-points mesh. These conditions of the q-points and the calculated spectral function have been successfully reported in the previous DFT studies 29 , 30 . Therefore, a 8 4 16 k -points and 2 2 2 q -points computed in the first Brillouin zone (BZ) were used.…”
Section: Methodssupporting
confidence: 63%
“…Ternary hydrides -or quaternary and higher -represent a new frontier where the search is on for superconducting materials that maintain dynamic stability to lower and lower pressures 147,152,153 . Thus far, investigation of ternary phase diagrams remains somewhat piecemeal, with only a few full convex hulls calculated 37,102,144,146,147,151,161 . The combinatorial possibilities for three elements generate a massive phase space that cannot be thoroughly investigated -whether by current experimental or theoretical techniques -on a reasonable timescale.…”
Section: Discussionmentioning
confidence: 99%
“…An additional study found that LaBeH 8 (in the same structure type) was dynamically stable down to 50 GPa, where its T c was estimated to be 191 GPa 147 . In addition to the La-B-H and La-Be-H structures, LaAlH 8 , CaBH 8 , and YBeH 8 were also found to be be dynamically stable at pressures below 100 GPa and LaBeH 8 , CaBH 8 , YBeH 8 , and SrBH 8 (dynamically stable above 210 GPa) were all found to lie on the convex hull 147 151 . In the former, the B@H 6 octahedra are arranged in an fcc lattice intercalated with Li atoms, resulting in an F m 3m structure that is stable down to 100 GPa.…”
Section: Ternary Hydride Materialsmentioning
confidence: 93%
“…The calculations were computed in the first BZ on k-points mesh and q-meshes, showing that it is sufficient to produce accurate electron-phonon coupling. Computational details of the electron-phonon and spectral function calculations were successfully reported in the theoretical studies 16 , 17 The Allen-Dynes equation 32 was exploited with the effective Coulomb pseudopotential parameter, .…”
Section: Methodsmentioning
confidence: 99%